(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Slangs are one of the most-used language variations. The bigger proportion of people who use slangs are youths. This research deals with slang and its interpretations. The study also counts reasons why nowadays teenagers choose colloquialisms for expression thoughts and feelings